Self-Efficacy Model for Elementary School Students: Case in Indonesia - Maksum, Arifin; Safitri, Desy; Ibrahim, Nurzengky; Marini, Arita; Wahyudi, Apri (Opción, 2019)
This study aim is to propose a model to develop student self-efficacy at elementary schools in in East Jakarta in Indonesia. This model pro- vided that student self-efficacy can be improved by level, strength, and generality. Data were collected from 204 students at Grade V from Jati 01, 05, 06, and 07 public elementary schools in East Jakarta in Indone- sia. Analysis data in this study used the Structural Equation Modeling (SEM). The study result found that level, strength, and generality are predictors of self-efficacy. Other finding also confirmed that students being able to finish the most difficult exam, students being able to cope with obstacles, students determining achievement target, students hav- ing motivation to do assignments, and students learning suitable with capabilities estimate level. Another finding suggested that students having stability to concentrate, students being resilient in doing task, students surviving to face obstacles, and students using all of their com- petences in finishing assignments influence strength. However, student rising up from a failure as a predictor of strength was not supported in this study. Students conducting variety of tasks, students finishing learning problems, students having commitments, student belief of their skills to achieve their goal, and student trust of their potencies belonged encourage generality.